Dictyosporella hydei sp. nov., an asexual species from freshwater habitats in China - Song, Hai-Yan; Huo, Guang-Hua; Hu, Dian-Ming (Phytotaxa, 2018)
A new species Dictyosporella hydei was collected on submerged wood in Yunnan Province, China. The new species is characterized by globose to broadly cylindrical, muriform and brass coloured conidia consisting of multiple angular, subglobose cells. Its affinity to Dictyosporella was inferred from phylogenetic analysis based on LSU data. The new species together with the other two species of Dictyosporella formed a well-supported clade which was closely related to Distoseptisporaceae.